Reframing the debate on legal financial obligations and crime: how accruing monetary sanctions impacts recidivism - Ostermann, Michael (Criminology, 2024)
Legal financial obligations (LFOs) associated with justice system involvement are increasingly a focus for policymakers and researchers seeking to understand sources of inequality and the factors that promote successful reentry. These conversations often rely on an assumption that LFOs are associated with or may even drive higher rates of recidivism. The empirical research in this area, however, has not kept up with the growing strength of these claims. This study reports findings that may offer a new perspective and contribute to an evidence-based debate. Multisourced administrative data on all individuals released from carceral supervision in an East Coast state (N = 21,301) over 3 years are used to examine the complex relationship between criminal justice debt and reoffending. We detail the results of survival analyses estimating the impact of these debts on various forms of recidivism. Broadly, we find that even though the relationship between case-level LFO assessments and future offending did not reach statistical significance, the association with the cumulative effect of monetary sanctions over the life course did. Furthermore, the impact of LFO debt is greater for certain racial groups, supporting theoretical and practical inquiries into factors informing structural disadvantage. Implications for policy and future research are considered.